Análise de patologias cardíacas - Oliveira, Bruno Samuel Luiz de (2018)
This work shows the development of a firmware in an embedded system capable of the analysis of cardiac electrical signals and shows via web server, an alert of cardiac pathologists diagnosed in the analyzed signals. As a differential, embedded system the Rasspberry Pi version 3 will be used for the tests and development of the proposed firmware. Describing the process necessary for the analysis and diagnosis of cardiac pathologies in order to obtain the filtering of the cardiac signal with subsequent detection of the R peaks, calculation of the heart rate and classification of cardiac pathologies. In order to investigate the processing capacity of the firmware, files with samples of signals containing some pathology were applied in the proposed firmware. Therefore, it is possible to verify the implementation of the mathematical treatments in cardiac signals, from the Python programming language, thus enabling the development of a firmware embedded in an electronic system, presenting a new methodology for the acquisition and processing of electrocardiographic signals, aiming at the diagnosis of cardiac pathologies and the sending of an alert of pathologies diagnosed in the analyzed signals through Web Server.